2020
DOI: 10.1021/acsearthspacechem.0c00057
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Processing of Anthropogenic Combustion Particles: Effects of Acid Media and Solar Flux on the Iron Mobility from Fly Ash

Abstract: Atmospheric combustion particles, such as fly ash emitted from coal-fired power plants, are a potential source of atmospheric iron, with significant implications in climate and global biogeochemical cycles. While the iron content and speciation of fly ash depend closely on the source region and combustion process, few studies have been carried out comparing the atmospheric processing of fly ash produced from coal-fired power plants in different regions. In this study, we present an investigation of iron dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 76 publications
(221 reference statements)
10
45
1
Order By: Relevance
“…Moreover, the new 3-step dissolution scheme better captured the initial fast dissolution of CFA (Figs. 2-3) which was also observed in previous research (Borgatta et al, 2016;Chen et al, 2012;Chen and Grassian, 2013;Fu et al, 2012;Kim et al, 2020) (except for the certified CFA 2689 in Chen et al (2012) which showed increasing dissolution rates over the duration of the experiment). Furthermore, the new scheme enabled us to account for the different Fe speciation determined in the CFA samples, which could be a key factor contributing to the different Fe dissolution behaviour observed in the present study and in literature (Borgatta et al, 2016;Chen et al, 2012;Chen and Grassian, 2013;Fu et al, 2012;Kim et al, 2020).…”
Section: Dissolution Behaviour Of Fe In Cfasupporting
confidence: 85%
See 2 more Smart Citations
“…Moreover, the new 3-step dissolution scheme better captured the initial fast dissolution of CFA (Figs. 2-3) which was also observed in previous research (Borgatta et al, 2016;Chen et al, 2012;Chen and Grassian, 2013;Fu et al, 2012;Kim et al, 2020) (except for the certified CFA 2689 in Chen et al (2012) which showed increasing dissolution rates over the duration of the experiment). Furthermore, the new scheme enabled us to account for the different Fe speciation determined in the CFA samples, which could be a key factor contributing to the different Fe dissolution behaviour observed in the present study and in literature (Borgatta et al, 2016;Chen et al, 2012;Chen and Grassian, 2013;Fu et al, 2012;Kim et al, 2020).…”
Section: Dissolution Behaviour Of Fe In Cfasupporting
confidence: 85%
“…compared the Fe solubility of CFA from USA Midwest, North-East India, and Europe in acidic solution (pH 1-2) containing 1 M NaCl. The Fe solubility measured after 24 hours varied from 15% to 70% in different CFA (bulk samples) at pH 2 with 1 M NaCl, which was considerably higher than that observed at pH 2 with 1 M NaNO3 (<20%) (Kim et al, 2020). Both studies did not investigate the impact of ionic strength on the dissolution behaviour, i.e., by comparing the dissolution at low and high ionic strength.…”
Section: Dissolution Behaviour Of Fe In Cfamentioning
confidence: 95%
See 1 more Smart Citation
“…Compared to the C 2 V structure, the less symmetric D 2 h is more reactive in the presence of solar radiation, which is consistent with the aforementioned heterogeneous photochemical pathway of adsorbed nitrates. Recently, Ostaszewski et al carried out QM calculations to simulate the vibrational spectra of nitric acid chemisorbed on TiO 2 , a semiconductor component of mineral dust and combustion particles with a bandgap of 403 nm, [ 32,158–160 ] which corresponds to an energy value below the atmospheric cutoff of solar radiation. [ 21 ] Similar to the calculations done on Al 2 O 3 , the geometry optimization and the vibrational frequencies were calculated using the B3LYP/6‐31 + G(d) level of theory, adjusted for anharmonicity factors.…”
Section: Surface Chemistry and Photochemistry Through Quantum Chemistrymentioning
confidence: 99%
“…These phases have a range of reactivities. Previous studies showed that CFA dissolves much faster during the first 1-2 hours than subsequently (Borgatta et al, 2016;Chen et al, 2012;Chen and Grassian, 2013;Fu et al, 2012;Kim et al, 2020), confirming the large difference in Fe dissolution from different phases.…”
Section: Introductionmentioning
confidence: 58%